Home Care for Improving Mother Breastfeeding Self Efficacy - Agrina; Erika; Sabrian, Febriana; Jumaini; Topia; Mutia, Sri; Patimah, Siti; Rizan, Eva (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The purpose of this study was to examine the influence of home care on increasing self efficacy in breastfeeding mothers.Method: This research was a quasi-experimental study non-equivalent control group design. The sample in this study were 30 breastfeeding mothers consisting of intervention and control groups taken by purposive sampling technique. The measuring instrument used in this study was breastfeeding self-efficacy short form (BSES-SF) scale consisting of 14 question items. The analysis used in this study is the dependent and independent T test.Result: The study results showed that the majority of respondents were in the young group (20-35 years old), the majority had high school education and a bachelor degree (80%), and mostly of respondent as a housewife (73.3%). Less than half of respondents (33.3%) immediately performed early breastfeeding initiation after deliver birth and as many as 25 babies (83.3%) received exclusive breastfeeding before starting this study. There was a mean difference in self-efficacy score in experimental group score of 62.27 with a standard deviation of 7.42 and the control group was 50.87 with a standard deviation of 4.76 after home care was done. There was a significant influence of home care on increasing breastfeeding mother’s self efficacy (p value